Oscillators with imaginary coupling: Spectral functions in quantum mechanics and quantum field theory - Mintz, Bruno W.; Pinheiro, Itai Y.; Aquino, Rui [UNESP] (American Physical Society (APS), 2025)
The axioms of quantum mechanics require that the Hamiltonian of any closed system is self-adjoint, so that energy levels are real and time evolution preserves probability. On the other hand, non-Hermitian Hamiltonians with PT symmetry can have both real spectra and unitary time evolution. In this paper, we study in detail a pair of quantum oscillators coupled by an imaginary bilinear term, both in quantum mechanics and in quantum field theory. We discuss explicitly how such Hamiltonians lead to perfectly sound physical theories with real spectra and unitary time evolution, in spite of their non-Hermiticity. We also analyze two-point correlation functions and their associated Källen-Lehmann representation. In particular, we discuss the intimate relation between positivity violation of the spectral functions and the nonobservability of operators in a given correlation function. Finally, we conjecture that positivity violation of some spectral functions of the theory could be a generic sign of the existence of complex pairs of energy eigenvalues (i.e., a PT-broken phase) somewhere in its parameter space.